Fabrication of nanochitosan incorporated polypyrrole/alginate conducting scaffold for neural tissue engineering - Asma Manzari-Tavakoli (Nature Portfolio, 2020)
Abstract The utilization of conductive polymers for fabrication of neural scaffolds have attracted much interest because of providing a microenvironment which can imitate nerve tissues. In this study, polypyrrole (PPy)–alginate (Alg) composites were prepared using different percentages of alginate and pyrrole by oxidative polymerization method using FeCl3 as an oxidant and electrical conductivity of composites were measured by four probe method. In addition, chitosan-based nanoparticles were synthesized by ionic gelation method and after characterization merged into PPy–Alg composite in order to fabricate a conductive, hydrophilic, processable and stable scaffold. Physiochemical characterization of nanochitosan/PPy–Alg scaffold such as electrical conductivity, porosity, swelling and degradation was investigated. Moreover, cytotoxicity and proliferation were examined by culturing OLN-93 neural and human dermal fibroblasts cells on the Nanochitosan/PPy–Alg scaffold. Due to the high conductivity, the film with ratio 2:10 (PPy–Alg) was recognized more suitable for fabrication of the final scaffold. Results from FT-IR and SEM, evaluation of porosity, swelling and degradation, as well as viability and proliferation of OLN-93 neural and fibroblast cells confirmed cytocompatiblity of the Nanochitosan/PPy–Alg scaffold. Based on the features of the constructed scaffold, Nanochitosan/PPy–Alg scaffold can be a proper candidate for neural tissue engineering.